Evaluasi pemeliharaan taman di areal jogging track dan playground, Pusat Pemerintahan Kabupaten Badung - Sanjaya, I Wayan Agus Rene; Semarajaya, Cokorda Gede Alit; Astawa, I Nyoman Gede (Jurnal Arsitektur Lansekap, 2021)
The use of plants in the jogging track and playground area at Puspem Badung is currently disrupting visitor activities because their growth has damaged pavements and facilities. Therefore, the implementation of garden maintenance is very important to be able to maintain the comfort of the visitors and the beauty of the garden. This study aims to evaluate the maintenance of the garden in the jogging track and playground area at Puspem Badung. The research method used is a survey method. The data collected in this study are primary data and secondary data. The data collection method is done by using observation, interview, questionnaire and literature study. Based on the research results, the implementation of maintenance is carried out independently by implementing an unit and special maintenance system. In the implementation of watering, pruning, silting and weeding activities, the performance of the workers exceeds the ideal working capacity standard except for sweeping and fertilizing activities. The perception of visitors to the physical condition of the garden is considered good, seen from the indicators of assessment including garden's cleanliness, pedestrian's cleanliness, cleanliness of benches, cleanliness of planter boxes, garden safety and the beauty of the garden. Suggestions in this research are that it is necessary to have a written standard operational procedures for garden maintenance and to propose tree pruning activities at least once every three months.